The Influence of Product Quality, Perceived Price and Brand Image Regarding the Purchase Decision of Specs Soccer Shoes - Wijanarko, Pandu Ardi; Wisnu, Dicky; Praharjo, Ardik (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
This study aims to examine and analyze the effect of product quality on purchasing decisions, perceived price on purchasing decisions, and brand image on purchasing decisions. The population in this study is the consumers of Specs soccer shoes with a sample size of 100 consumers. The sampling technique uses accidental sampling. Data collection techniques in this study used a questionnaire. The analytical tool in this study uses scale range and multiple linear analysis. Based on the test results, this study concluded that product quality, perceived price, and brand image had a positive and significant effect on purchasing decisions. Product quality had a dominant effect on purchasing decisions for Specs soccer shoes.